Pengaruh Kemudahan dan Religiusitas terhadap Keputusan Pembelian Menggunakan Paylater pada Marketplace Shopee pada Mahasiswa IIQ An Nur Yogyakarta - Na’im, Ani; Solikhah, Puji; Mawftiq, Rarasati (Quranomic: Jurnal Ekonomi dan Bisnis Islam, 2023)
This study raises the issue of the effect of convenience and religiosity on purchasing decisions using a paylater on the shopee marketplace. The purpose of the study was to determine the effect of convenience on purchasing decisions using paylater on the shopee marketplace, and the influence of religiosity on purchasing decisions using paylater on the shopee marketplace. And to find out the effect of convenience and religiosity with purchasing decisions using a paylater on the shopee marketplace. The results showed that partially Ease (X1) did not affect the decision to use paylater, because the t-count > t-table (-2.705 < 1.98552) with a significance value of 0.08 > 0.05. Religiosity (X2) has a significant impact on the decision to use a paylater, because the t-count > t-table (4.220 > 1.98552) with a significance value of 0.00 <0.05. So that there is a significant effect between the X1 variable on Y, or in other words H0 is rejected and Ha is accepted. Meanwhile, simultaneously obtained F count 9.124 and a significant value of 0.000. The results of data processing showed a significant value at 0.0000 (sig 0.00000 <0.05).